2008
DOI: 10.1371/journal.pone.0001494
|View full text |Cite
|
Sign up to set email alerts
|

Coronavirus Spike Protein Inhibits Host Cell Translation by Interaction with eIF3f

Abstract: In response to viral infection, the expression of numerous host genes, including predominantly a number of proinflammatory cytokines and chemokines, is usually up-regulated at both transcriptional and translational levels. It was noted that in cells infected with coronavirus, transcription and translation of some of these genes were differentially induced. Drastic induction of their expression at the transcriptional level was observed in cells infected with coronavirus. However, induction of the same genes at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
70
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(74 citation statements)
references
References 38 publications
3
70
0
1
Order By: Relevance
“…However, eIF3-f is essential for Schizosaccharomyces pombe viability, and its depletion markedly decreases the global protein synthesis in fission yeast (11). The same effect on protein translation was recently described in cells infected with the coronaviruses severe acute respiratory syndrome coronavirus (SARS coV) and coronavirus infectious bronchitis virus (12). In humans, down-regulation of eIF3-f is associated with several tumors (13,14), and when overexpressed, eIF3-f negatively regulates cell growth by affecting translation efficiency and activation of apoptosis (15).…”
mentioning
confidence: 55%
“…However, eIF3-f is essential for Schizosaccharomyces pombe viability, and its depletion markedly decreases the global protein synthesis in fission yeast (11). The same effect on protein translation was recently described in cells infected with the coronaviruses severe acute respiratory syndrome coronavirus (SARS coV) and coronavirus infectious bronchitis virus (12). In humans, down-regulation of eIF3-f is associated with several tumors (13,14), and when overexpressed, eIF3-f negatively regulates cell growth by affecting translation efficiency and activation of apoptosis (15).…”
mentioning
confidence: 55%
“…Antibodies against Myc and FLAG were from Sigma, and antibodies against actin were from Santa Cruz (Santa Cruz, CA). Polyclonal antibodies against IBV N and S proteins were raised in rabbits (40,41). Mouse antibodies against HA for indirect immunofluorescence assays was from ETC (Singapore).…”
Section: Methodsmentioning
confidence: 99%
“…In addition, the spike (S) protein of SARS-CoV and infectious bronchitis virus (IBV) can interact with eIF3f to inhibit host translation. This mechanism has been exploited by coronaviruses to counteract the host-antiviral response and to modulate coronavirus pathogenesis (Xiao et al, 2008). Wataru Kamitani had reported that the nsp1 protein of SARS-Cov utilizes a twopronged strategy to inhibit translation of host proteins: nsp1 blocked the formation of 80S by binding to the 40S ribosomal subunit and facilitated the degradation of the 5ā€²-end of mRNA degradation, rendering the mRNA translationally inactive (Kamitani et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…For example, the rabies virus (RV) M protein can inhibit eukaryotic translation via a protein interaction with eIF3 h (Komarova et al, 2007). Furthermore, eIF3f can also interact with the S protein of SARS-CoV and infectious bronchitis virus (IBV) to inhibit expression of host genes (Xiao et al, 2008). In addition to inhibiting host translation, eIF3f can inhibit HIV replication by specifically impeding the 3ā€² end processing of HIV-1 mRNAs (Valente et al, 2009).…”
Section: Introductionmentioning
confidence: 99%